Illustration of Online Learning Motivation for Students in Grades III-VI During the Covid-19 Pandemic at SD Dolok Huluan, Simalungun Regency In 2021 - Manalu, Wenny Lestari (Jurnal EduHealth, 2022)
Background: Online learning motivation is a supporting factor that makes a person willing and happy to mobilize all abilities, expertise and skills possessed to carry out activities that are their obligations to achieve the desired goals. The importance of learning motivation for elementary school children is so that students remain motivated to continue their education. Students' learning motivation will increase if they have motivation that comes from within themselves and there is support from the surrounding environment. Methods: The research design used is descriptive research. The sampling technique in this study used total sampling with a total sample of 92 respondents. The instrument used is a questionnaire sheet on online learning motivation variables. Results: The results showed that the online learning motivation of grade III-VI students during the covid-19 pandemic at SD Dolok Huluan, Simalungn Regency in 2021 was mostly in the high category, namely 52.2%. Discussion: Based on the results obtained, it can be concluded that students' learning motivation remains high even though the covid-19 pandemic is endemic. It is hoped that this research can be an input for all students and education staff to keep paying attention to students' learning motivation during online learning.